2001
DOI: 10.4049/jimmunol.167.11.6113
|View full text |Cite
|
Sign up to set email alerts
|

CD18 Activation Epitopes Induced by Leukocyte Activation

Abstract: The cell surface adhesion molecule LFA-1 coordinates leukocyte trafficking and is a costimulatory molecule for T cell activation. We developed a panel of mAbs that recognize activation epitopes on the CD18 subunit, and show that stimulation of T lymphocytes appears to be accompanied by a conformational change in a subpopulation of LFA-1 that does not require ligand binding. Activation epitope up-regulation requires divalent cations, is sensitive to cellular signal transduction events, and correlates with cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 40 publications
2
81
0
Order By: Relevance
“…Although the underlying mechanism for inside-out signaling remains elusive, the conformational changes within the CD11b/ CD18 receptor that occur as a result of cell activation have been well documented (33,34,44,45). Relevant to this study, it was reported that PMA stimulation of peripheral leukocytes leads to the expression of a neo-epitope on CD11b/CD18, which can be probed by an activation-dependent mAb, MEM148 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism for inside-out signaling remains elusive, the conformational changes within the CD11b/ CD18 receptor that occur as a result of cell activation have been well documented (33,34,44,45). Relevant to this study, it was reported that PMA stimulation of peripheral leukocytes leads to the expression of a neo-epitope on CD11b/CD18, which can be probed by an activation-dependent mAb, MEM148 (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PMA induces phosphorylation of Thr 758 in the ␤ 2 chain of LFA-1, which can modulate LFA-1 interactions with the actin cytoskeleton (62,63). Previous studies tested the effect of PMA on LFA-1 activity after prolonged exposure periods (10 -30 min) and demonstrated that this stimulation induces LFA-1 conformational changes detected by various reporter mAbs (10,19,21,64). Importantly, although 1 min stimulation of T cells with PMA is sufficient to trigger rapid LFA-1 adhesiveness to ICAM-1, it does not induce conformational changes of LFA-1.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-␤ 2 integrin extension epitope KIM127 was a gift from M. K. Robinson (UCB-Celltech, Slough, U.K.). The LFA-1 Idomain allosteric IDAS-specific inhibitor A308926 and its control compound A270412 were gifts from D. Staunton (21). TS2.4-Alexa568 was a gift from F. W. Luscinskas (Harvard Medical School, Boston, MA).…”
Section: Reagents and Mabsmentioning
confidence: 99%
“…7E4 could bind to bent α X β 2 , in agreement with the presence of the closed headpiece in the bent conformation of α X β 2 (4). TS1/18 also blocks β 2 integrin activation on intact cells (27,35). This mAb binds to the residues on the α1-and α7-helices in the βI domain (Fig.…”
Section: Discussionmentioning
confidence: 99%